Selection of a Propellant Feed System for the LPRE of a Small Upper Stage (International Journal of Mathematics and Physics, 2025)
The design of small upper stages must meet many propulsion requirements: repeated restarts, stable operation at low mass flow rate, strict limits on mass and volume, and compatibility with limited ground infrastructure. The central engineering task is a justified selection of the liquid propellant rocket engine feed architecture for a given mission profile and propellant pair, since this choice affects specific impulse, service life, risk, and ground processing effort. This work systematizes propellant feed schemes for a small upper stage and proposes a unified analytical framework that links engine cycle and feed method with propellant selection and tank pressurization modes. Pressure fed and turbopump schemes are treated as mature solutions; pump cycles are used mainly with cryogenic propellants and in high energy demand cases that require high efficiency and compact hardware. In parallel, electro pump schemes are actively studied as a promising direction due to lower mechanical complexity, precise control, and straightforward integration with modern control systems. The analysis shows how chamber pressure, allowable throttling range, restart capability, and the mass and volume metrics of tanks and hardware bound the rational domain of each scheme. The outcome is a set of criteria for early design that maps mission requirements to feed system architecture and supports a technologically feasible choice for small upper stages.Keywords: pressure-fed system, turbopump-fed supply system, small upper stages, rocket engines, liquid rocket engine.